Effects of High-Rate Frequency Modulation Treatment on Malondialdehyde in Diabetic Polyneuropathy - KAVAK*, S.; DULGER†, H.; TULGAR‡, M.; ALKIS§, I. (Asian Journal of Chemistry, 2009)
This study is planned to investigate the effects of transcutaneous electrical nerve stimulation (TENS) treatment on patients which have diabetic polyneuropathy. Fourteen diabetic polyneuropathy patients suffering ischemic pain were examined during the cure. Malondialdehyde (MDA) and glycemia levels were determined by collecting 5 mL blood samples from 14 patients 24 h before beginning the treatment. In case 50 Hz signals as high-rate frequency modulation (HRFM; continuous pulses changed from 90 Hz to 55 Hz over 90 msec, 1.3 times a second), were applied to patients as long as 20 d for 20 min a day. Transcutaneous electrical nerve stimulation (TENS) treatment increased significantly free oxygen radicals (p < 0.05). The levels of MDA before TENS were compared to the levels of MDA after TENS and the end of the following term of 20 days by paired sample test and a meaningful increase was seen significantly (p < 0.01). Besides, glycemia levels were decreased significantly before TENS-after TENS treatment (p < 0.01) and not changed before TENS and the end of the following term of 20 d (p > 0.05). Moreover, it was observed that MDA levels were decreased significantly between in the final of the treatment and the end of the following term of 20 d (p < 0.01). Glycemia levels were not changed significantly after TENS and the end of the following term of 20 d (p > 0.05). According to this results, it is observed that TENS treatment has been positive effect on polyneuropathy.